Linking phytochrome to plant immunity: low red : far-red ratios increase Arabidopsis susceptibility to Botrytis cinerea by reducing the biosynthesis of indolic glucosinolates and camalexin - Cargnel, Miriam D. (2014)
Shade-intolerant plants respond to low red : far-red (R : FR) ratios, which signal the proximity of potential competitors, by down-regulating immune responses. Here we investigated the mechanisms underlying this immune suppression in Arabidopsis. We used genetic, transcriptomic and metabolomic approaches to examine the functional connections between R : FR ratio and Arabidopsis resistance to the fungus Botrytis cinerea. Low R : FR ratios reduced the concentration of indol-3-ylmethyl glucosinolate (I3M) (an indolic glucosinolate, iGS) and camalexin in plants inoculated with B. cinerea, and attenuated the I3M response triggered by jasmonate elicitation. These effects on metabolite abundance correlated with reduced expression of iGS and camalexin biosynthetic genes. Furthermore, the effect of low R : FR increasing Arabidopsis susceptibility to B. cinerea was not present in mutants deficient in the biosynthesis of camalexin (pad3) or metabolism of iGS (pen2). Finally, in a mutant deficient in the JASMONATE ZIM DOMAIN-10 (JAZ10) protein, which does not respond to low R : FR with increased susceptibility to B. cinerea, supplemental FR failed to down-regulate iGS production. These results indicate that suppression of Arabidopsis immunity against B. cinerea by low R : FR ratios is mediated by reduced levels of Trp-derived defenses, and provide further evidence for a functional role of JAZ10 in the link between phytochrome and jasmonate signaling.